همُّ النبي -صلى الله عليه وسلم -وأثره في الإستدلال الفقهي و التعليل الأصو ل - سيرين دومة; هاجر عراوة; د/محمد عيشوبة (جامعة عمار ثليجي الاغواط, 2023)
الملخص: تعدُّ السنة النبوية المصدر التشريعي الثاني بعد القرآن الكريم، فكل ما صدر عن النبي -صلى الله عليه وسلم-من أقوال وأفعال وتقري ا رت،اعتبره الأصوليون صالحا للإستنباط فأخذوا من أحاديثه قواعد وأحكام يقوم عليها هذا الدين العظيم ، وقد وردت أحاديث هي ضمن همه -عليه الصلاة والسلام-اختلف الأصوليون والفقهاء في اِعتبارها دليلا ودلالة. 151 وقد توصلت د ا رستنا هذه إلى بيان أثر الخلاف بين الأصوليين والفقهاء في حجية ه مِ النبي -صلى الله عليه وسلم – ومدى حجيته واستنباط الأحكام التشريعية منه،وأثر ذلك عند مختلف المدارس الفقهية والأصولية . الكلمات المفتاحية :الهم النبوي - -السنة النبوية-التنوع الفقهي- التنوع الأصولي - الأثر. Abstract : The Sunnah of the Prophet is the second legislative source after the Holy Qur’an. All that was issued by the Prophet - may God bless him and grant him peace - in terms of sayings, deeds and reports. Fundamentalists and jurists differed in considering it as evidence and indication. Our study has reached a statement of the impact of the disagreement between the fundamentalists and the jurists on the authoritative will of the Prophet - may God bless him and grant him peace - and the extent of his authoritativeness and the deduction of legislative rulings from him, and the impact of that on the various schools of jurisprudence and fundamentalism . Keywords: The Prophet's Will - The Prophet's Sunnah - Jurisprudential Diversity - Fundamental Diversity - Impact